The effect of five price categories in tick size policy on trade and stock returns based on the LQ45 Index - Nurlaila Firdani Fajri; Hermanto Siregar; Ferry Syarifuddin (University of Merdeka Malang, 2019)
The capital market has an influential role in the national economy of countries, including Indonesia. The capital market in Indonesia is regulated by the Indonesia Stock Exchange (IDX) with the new regulation number Kep-00113/BEI/12-2016 that focuses on five price categories of tick size. This study aimed to investigate the impact of five price categories in tick size policy on liquidity and volatility based on the LQ45 index and examine factors that influence stock return. This study was performed using a paired sample T-test and panel regression test. The result of the different test indicates a significant change in bid-ask spread, Depth, Depth to relative spread (DRS), volume, and volatility. The five price category in the tick size policy does not affect the depth. It is found that all the variables have a smaller value after the implementation of the tick size policy. The results of the panel regression test show that depth, volume, and volatility have a significant influence on stock returns, while the bid-ask spread, and DRS does not affect stock returns. The result of this study was expected to improve understanding of the tick size regulation to determine the best stock investment strategy.JEL Classification: G11, G12, G23, R53DOI: https://doi.org/10.26905/jkdp.v23i1.2598